Evaluation of the Factors that Have the Most Significant Influence on Lithuanian Export - Rita Remeikiene; Ligita Gaspareniene; Alius Sadeckas (Institute of Economic Research (IER), 2017)
Export is an important part of economics not only in a country's, but also in international level. Over the last two decades, development of export has been one of the fastest and most acceptable strategies of economic progress. Export is also one of the ways to improve a country's balance of payments, reduce trade deficits, and raise the general life standards. Scientific literature does not contain any unambiguous models developed for evaluation of the impact of the influential factors on the volumes of exports in the countries with similar economic conditions. Hence, the scientific problem for this research is formulated as follows: which factors have the most significant impact on export and how does this impact manifest? is to conduct evaluation of the influential factors affecting Lithuanian export leaning on the theoretical aspects of export determinants. The methods of the research include comparative and systematic analysis of the scientific literature, correlation and regression analysis. Mathematical estimations have revealed that GDP per capita and general state's revenue from taxes and social contributions can explain the trends of Lithuanian export by 99.1 percent over the period 2007 - 2015. Crediting of private sector also showed a very strong correlation with Lithuanian export; the negative medium-strong correlation was estimated between the export and general tax level, while the positive medium-strong correlation was captured between the export and minimum wages.
Keywords: J11; O15; 330; export; factors; evaluation; Lithuania